Service learning: a cutting-edge teaching and learning methodology embracing social action with critical inquiry and classroom work - Mikelić Preradović, Nives (2009)
The workshop deals with new educational methodology that transforms the old teaching style and gives student more place to apply theory they learned, while in the same time they think how to solve world problems. The workshop deals with methods of integration of that methodology with ICT in order to achieve better learning outcomes. It also presents the service learning projects in Croatian university.